2017
DOI: 10.1016/j.chemosphere.2016.12.133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an anaerobic feed and split anaerobic–aerobic feed on granular sludge development, performance and ecology

Abstract: The retrofitting of existing wastewater sequencing batch reactors (SBRs) to select for rapid-settling aerobic granular sludge (AGS) over floc-based conventional activated sludge (CAS), could be a viable option to decrease reactor cycle time and increase hydraulic capacity. Successful CAS-to-AGS conversion has previously been shown to be highly dependent on having a dedicated anaerobic feed, which presents additional engineering challenges when retrofitting SBRs. In this study we compared the performance of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Pulse feeding followed by anaerobic mixing allows for the formation of stable granules due to the stable growth rate, which allows for a suitable balance between the growth of heterotrophic and autotrophic microorganisms [22]. Nevertheless, while one study found the split anaerobic-aerobic feeding strategy suitable for aerobic granule formation and stable granules at low organic loading rate [23], another study reported the contrary [24].…”
Section: Introductionmentioning
confidence: 99%
“…Pulse feeding followed by anaerobic mixing allows for the formation of stable granules due to the stable growth rate, which allows for a suitable balance between the growth of heterotrophic and autotrophic microorganisms [22]. Nevertheless, while one study found the split anaerobic-aerobic feeding strategy suitable for aerobic granule formation and stable granules at low organic loading rate [23], another study reported the contrary [24].…”
Section: Introductionmentioning
confidence: 99%
“…A rising number of full‐scale sequencing batch reactors (SBRs) are operated using the commercial Nereda process, which is reported to be more cost‐efficient compared to the conventional wastewater treatment technology with an overall lower energy consumption . Although numerous studies have focused on the process stability and treatment performance of AGS cultivated under laboratory‐scale as well as under full‐scale conditions, information about the impacts on advanced sludge stabilization is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the biological processes have been explored in terms of biomass composition (bacteria, protozoa, metazoan, and fungi) and activity: conventional activated sludge, attached biomass, membrane reactors, and treating either municipal [27][28][29][30][31][32][33][34] or industrial wastewater [35][36][37][38][39]. Likewise, identification and quantification of microorganisms operating under different conditions (aerobic, anoxic, and anaerobic) have been reported [25,[40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%